2017
DOI: 10.5194/tc-11-2829-2017
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Arctic sea ice drift and strength modelled by NEMO-LIM3.6

Abstract: Abstract. Sea ice cover and thickness have substantially decreased in the Arctic Ocean since the beginning of the satellite era. As a result, sea ice strength has been reduced, allowing more deformation and fracturing and leading to increased sea ice drift speed. We use the version 3.6 of the global ocean-sea ice NEMO-LIM model (Nucleus for European Modelling of the Ocean coupled to the Louvain-laNeuve sea Ice Model), satellite, buoy and submarine observations, as well as reanalysis data over the period from 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 62 publications
4
35
2
Order By: Relevance
“…Computing drift speed from monthly mean components (i.e., trueu¯i2+truev¯i2), produces drift speeds that are about a factor of two lower than in Figure (not shown). Docquier et al () have shown a similar effect of temporal sampling on the computation of sea ice drift speed in one particular model. In some models, temporal sampling also affects the apparent timing of the seasonal peak of sea ice drift speed.…”
Section: Evaluation Of Model Drift Speedmentioning
confidence: 78%
See 4 more Smart Citations
“…Computing drift speed from monthly mean components (i.e., trueu¯i2+truev¯i2), produces drift speeds that are about a factor of two lower than in Figure (not shown). Docquier et al () have shown a similar effect of temporal sampling on the computation of sea ice drift speed in one particular model. In some models, temporal sampling also affects the apparent timing of the seasonal peak of sea ice drift speed.…”
Section: Evaluation Of Model Drift Speedmentioning
confidence: 78%
“…This sea ice thinning leads to a reduction in sea ice strength, which reduces the sea ice internal stress, allowing for more sea ice deformation, more fracturing, and faster drift. Evidence for such a physical mechanism has been shown in models (Docquier et al, ) and observations (Rampal et al, ; Spreen et al, ). In GFDL‐CM3, the trend of sea ice thickness is approximately −0.3 m dec −1 in the Western Arctic, and the drift speed trend is approximately 0.7 km d −1 dec −1 in this region.…”
Section: Drivers Of Long‐term Trends During Wintermentioning
confidence: 89%
See 3 more Smart Citations